2004
DOI: 10.1074/jbc.m408362200
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin Signaling and Organization in Heterozygote Rhodopsin Knockout Mice

Abstract: Rhodopsin (Rho) resides within internal membrane structures called disc membranes that are found in the rod outer segments (ROS) of photoreceptors in the retina. Rho expression is essential for formation of ROS, which are absent in knockout Rho؊/؊ mice. ROS of mice heterozygous for the Rho gene deletion (Rho؉/؊) may have a lower Rho density than wild type (WT) membranes, or the ROS structure may be reduced in size due to lower Rho expression. Here, we present evidence that the smaller volume of ROS from hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
149
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 141 publications
(167 citation statements)
references
References 50 publications
(58 reference statements)
16
149
2
Order By: Relevance
“…Importantly, the imaging experiments were performed in a native setting with undisturbed intact eyes, which avoided potential artifacts arising from required tissue-processing. Although ROS sizes are known to be determined by rhodopsin content (75)(76)(77)(78), these light-induced changes were too rapid for de novo protein biosynthesis to account for them. Additionally, it had been shown that rhodopsin mislocalized significantly to rod inner segments only at 48 h after light-induced damage (74).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the imaging experiments were performed in a native setting with undisturbed intact eyes, which avoided potential artifacts arising from required tissue-processing. Although ROS sizes are known to be determined by rhodopsin content (75)(76)(77)(78), these light-induced changes were too rapid for de novo protein biosynthesis to account for them. Additionally, it had been shown that rhodopsin mislocalized significantly to rod inner segments only at 48 h after light-induced damage (74).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from Test Flashes as Determined by Paired Flash Analysis-A paired flash protocol was used to evaluate the ability of GC deletion mutant retinas to recover responsiveness after light stimulation (23,30,35). In this method, short test flashes followed by varying interstimulus intervals, and a probe flash were used to test for a-wave recovery (36,37).…”
Section: Generation Of Gc2mentioning
confidence: 99%
“…Leading edges of the ERG responses were fitted with a model of rod photoreceptor activation (29). The double-flash recording followed a previously published protocol (30). The normalized amplitude of the probe flash a-wave versus the time between two flashes was plotted and fit by the linear regression algorithm in the SigmaPlot program (version 9.0).…”
Section: Construction Of Targeting Vector and Generation Of Gc2mentioning
confidence: 99%
“…The ROS of heterozygous mice for the rhodopsin gene deletion (rhodopsin ϩ/Ϫ ) have a similar density of rhodopsin, but their rhodopsin volume is reduced by ϳ60% when compared with wild-type mice (6). Synthesis of opsin begins in the inner segments of photoreceptors, where it undergoes maturation in the endoplasmic reticulum and Golgi membranes before being vectorially transported to the ROS.…”
Section: Rod Outer Segment and Rhodopsinmentioning
confidence: 99%
“…For example, Asn-55 of TM helix I, Asn-78 and Asp-83 of TM helix II, and Asn-302, Pro-303, and Tyr-306 of TM helix VII (part of the NPXXY(X) 5,6 F motif) are all highly conserved amino acids across the GPCR family that appear to form important contacts for maintaining the inactive state of rhodopsin. FIGURE 1.…”
Section: Structure Of Rhodopsinmentioning
confidence: 99%